Bibliometric evaluation of 2020–2022 publications on COVID-19-related cardiovascular disease - Chen, Yiru; Cao, Buzi; Zhou, Quan; Liu, Yantong; He, Qingnan; Zhao, Mingyi (Frontiers in Cardiovascular Medicine, 2023)
Objective: The purpose of this study was to investigate the international scientific output of cardiovascular disease in COVID-19 research through a bibliometric analysis and to explore research hotspots in this field. Methods: We searched the Web of Science Core Collection for publications and used many kinds of software to analyse and visualize the data such as R, CiteSpace and VOSviewer. Results: A total of 10055 publications were retrieved as of December 13, 2022 based on the inclusion criteria after screening. The United States and China lead in the quantity and quality of publications in this field. Based on Bradford’s Law, 63 journals are considered core journals in the field. Co-cited references and keywords analysis indicate researchers’ attention to cardiovascular comorbidities, outcomes and regenerative medicine of COVID-19. In summary, with increasing COVID-19 research related to CVD, more attention might be given to the relationship between these two diseases. Conclusion: The hotspots in this field may continue to revolve around cardiovascular comorbidities, outcomes and regenerative medicine of COVID-19. Due to the different situations faced by different groups under COVID-19, further exploration of the related factors specific for different groups such as patients with previous heart failure and patients without previous heart failure are needed, with a hopeful view to providing reference for intervention measures in COVID-19 research.